Microcrédito e empoderamento de mulheres de baixa renda: uma análise do projeto “Elas” - Cezar, Irina Frare (2016)
Microcredit has been a tool to combat poverty around the world in recent decades. Increased access to credit to those who cannot appeal to the traditional financial system has constituted a democratic way of promoting social inclusion through the generation of jobs and income. The loans made have shown beneficial effects on low-income communities, particularly in relation to women, by triggering an empowerment process with effects on their ability to earn income, improve their self-esteem and increase their participation in decision-making spaces. In Brazil, women are the majority of microcredit borrowers, and the justification for it, goes through the difficulties in the formal market, the need to supplement the family income, the desire for greater emancipation front of the companions and the search for self-realization in a small enterprise. In Fortaleza (CE), Banco Palmas created a gender empowerment project, focused on beneficiaries of the Bolsa Família, from the microcredit. This work aimed to analyze the dimensions of the process of empowerment achieved by women participating in this project, entitled project 'ELAS'. The initial hypothesis was that the new economically productive capacity of respondents would change their reality, putting them at a new level before themselves and their families, providing greater autonomy in their decisions and financial independence before their husbands, besides the increase of their welfare. In this case, microcredit would serve as a promoter of women's individual empowerment – hypothesis demonstrated in this study. However, it was noted that there has not been a breach of gender relations within the families, especially apparent factor for non-redistribution of household tasks, with restrictive impact on social empowerment of women through non-participation in instances of collective decision-making.